EFL Students' Perceptions of Social Issues in Famous Works of Art - Lizmendy Zuhey Bautista Urrego; Ingrid Judith Parra Toro (Asociación Colombiana de Profesores de Ingles, 2016)
This article reports on a qualitative, descriptive, and interpretative research intervention case study of English as a foreign language students' construction of perceptions on social issues found in famous works of art. Participants in this study engaged in the practice of critical thinking as a strategy to appreciate art that expresses social issues. The research was conducted at a Colombian public school over ten days. Famous works of art were presented with the purpose of creating a conversation club in which students were expected to identify and discuss social issues implicit in those works of art. Data were collected through direct observation, field notes, and interviews. Findings showed participants' perceptions of works of art while interacting in English conversations.